MARKETING MIX TERHADAP LOYALITAS PELANGGAN ENCENG GONDOK DI DAERAH GROYOK KABUPATEN LAMONGAN - NURUL FAUZIYAH, SITI (Jurnal Pendidikan Tata Niaga (JPTN), 2013)
The research was conducted at the Regional Groyok Lamongan. This type of research is a survey method with the quantitative approach. The population of water hyacinth in the customer area and Lamongan Groyok sample of 100 respondents. Data was collected through questionnaire method and documentation. Data analysis techniques used in this research using multiple linear regression analysis. The results of this study indicate that the effect of the product, pricing, distribution channels, and promotion of customer loyalty water hyacinth products is quite high. While the quality of the product simultaneously be the most dominant factor in influencing customer loyalty. Key word :marketing mix,customer loyalty